Anti-cancer mechanisms of linalool and 1,8-cineole in non-small cell lung cancer A549 cells - Rodenak Kladniew, Boris Emilio (2020)
Linalool and 1,8-cineole are plant-derived isoprenoids with anticancer activities in lung cancer cells, nevertheless, the cellular and molecular mechanisms of action remain poorly understood. The purpose of this study was to determine the anticancer mechanisms of action of linalool and 1,8-cineole in lung adenocarcinoma A549 cells. Linalool (0–2.0 mM) and 1,8-cineole (0–8.0 mM) inhibited cell proliferation by inducing G0/G1 and/or G2/M cell cycle arrest without affecting cell viability of normal lung WI-38 cells. None of the two monoterpenes were able to induce apoptosis, as observed by the lack of caspase-3 and caspase-9 activation, PARP cleavage, and DNA fragmentation. Linalool, but not 1,8-cineole, increased reactive oxygen species production and mitochondrial membrane potential depolarization. Reactive oxygen species were involved in cell growth inhibition and mitochondrial depolarization induced by linalool since the antioxidant N-acetyl-L-cysteine prevented both effects. Besides, linalool (2.0 mM) and 1,8-cineole (8.0 mM) inhibited A549 cell migration. The combination of each monoterpene with simvastatin increased the G0/G1 cell cycle arrest and sensitized cells to apoptosis compared with simvastatin alone. Our results showed that both monoterpenes might be promising anticancer agents with antiproliferative, anti-metastatic, and sensitizer properties for lung cancer therapy.